THE NEW GENERATION OF EMPLOYEE BEHAVIOR: QUIET QUITTING (Third Sector Social Economic Review, 2024)
Organizations are legal entities that are founded on the motivation of being transferred from generation to generation and providing continuity, aiming to exist as a pioneer in their field with their profitability, and showing vitality with their dynamic structure and the idea of continuity. This living structure of organizations helps them to protect themselves similar to humans, to create and realize plans and projects in accordance with the requirements of the conditions with research and development methods, to maintain their effectiveness in a mass sense, to make decisions in line with target/result relations and analysis, and to ensure their continuity as a result of the right decisions. From this point of view, the departments in the organizational structure represent the organs in the body of a concrete living being, while the employees within the department represent a part of the building blocks that fulfill the functions of these organs. For this reason, the vital continuity of the organization and the healthy functioning of its functions are directly dependent on the employees and their behaviors. The importance of the behaviors exhibited by employees, who are the building blocks of the organization, has been understood by organizations today, and in this direction, organizations have started to take supportive measures in organizational behavior and to show the necessary efforts to ensure employee motivation and job satisfaction. The concept of silent resignation is a peaceful phenomenon, behavior or defense mechanism, put forward by employees for various reasons in response to the desire and spirit of duty that the organization demands more than necessary and expected. Although this situation seems to be a normal situation for working individuals, it can lead to negative consequences for the organization. Within the scope of this research, the emergence of the concept of quiet quitting, its detailed definition and theoretical examination will be made, and the factors affecting the concept will be discussed and suggestions will be made about its organizational risks and prevention.
Keywords: Organization; Organizational Behavior; Employee Behavior; Quiet Quitting; Quiet Resignation.